2012
DOI: 10.1108/01409171211210118
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and job‐related learning

Abstract: Various empirical studies have examined transformational leadership on the effects of followers and organisations. Transformational leadership has been related to individual attitudes and behaviors such as satisfaction with leaders, organisational citizenship behavior, organisational commitment, motivation, trust in leader, creativity, performance, employee involvement, and empowerment. It has also been linked to such organisational outcomes as innovation, change, productivity, ethical climate, and organisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…This finding is in line with earlier studies, which demonstrate the influence of leadership on employees' learning behaviour and motivation to learn (Loon et al . ). Moreover, our results confirm the positive relationship between leadership and vitality (Hamilton & Schriesheim ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding is in line with earlier studies, which demonstrate the influence of leadership on employees' learning behaviour and motivation to learn (Loon et al . ). Moreover, our results confirm the positive relationship between leadership and vitality (Hamilton & Schriesheim ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have also suggested an association between leadership and job related learning (Loon et al . ) and between leadership and vitality at work (Carmeli et al . ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Additionally, leaders are responsible for creating a climate that is conducive to learning (Castiglione, 2006; Loon et al, 2012). When leaders possess considerable emotional skills in addition to technical competence, they can motivate employees by providing them a psychologically safe environment (Pisano et al, 2001).…”
Section: Models Of Emotional Intelligencementioning
confidence: 99%
“…In general, these studies use questionnaires and survey data to examine the occurrence of transformational leadership and its correlations with learning and organizational performance (cf. Raes et al, 2013;Loon et al, 2012;Thuy Pham & Swierczek, 2006). In line with Bass's model, these studies find that transformational behaviours are positively linked to learning and innovation, whereas transactional behaviours are not (Amitay, Popper & Lipshitz, 2005;Jung, Chow & Wu, 2003).…”
Section: The Normative Approachmentioning
confidence: 99%
“…In this respect, the support from managers has especially been highlighted as important for promoting and enhancing individual and collective learning (Eraut, 2011;Loon, Mee Lim, Heang Lee & Lian Tam, 2012). Popular designations for this new leadership are transformational and transactional leadership (Bass, 2000;Loon et al, 2012), developmental leadership (Gilley, Shelton & Gilley, 2011;Larsson et al, 2003), managers as teachers (Agashae & Bratton, 2001), managers as facilitators of learning (Cohen, 2013;Ellinger & Bostrom, 2002), managers as developers (Warhurst, 2013), and managers as coaches (Ladyshewsky, 2010).…”
Section: Introductionmentioning
confidence: 99%